P3_4 Reducing blood loss through injury - Patel, Poonam; Patel, Jessica; Joshi, Rutambhara (Physics Special Topics, 2014)
On event of sustaining an injury which results in bleeding, it is advised to apply pressure on the wound and also elevate the injury above the height of the heart [1]. This paper investigates the physics behind the two actions, and shows that both cases result in the decreasing of the volumetric flow rate, and hence reduce the rate at which blood is lost.